Computer-generated real-time digital holography: first time use in clinical medical imaging. (9th June 2016) - Bruckheimer, Elchanan; Rotschild, Carmel; Dagan, Tamir; Amir, Gabriel; Kaufman, Aviad; Gelman, Shaul; Birk, Einat
Abstract: Aims: Assessment of the feasibility of creating real-time interactive 3D digital holograms in a standard catheterization laboratory. 3D medical images are typically displayed and interacted with on 2D screens limiting their usefulness. A digital computer-generated real-time holographic display of patient's 3D data could provide a spatially accurate image with all the depth cues and afford interaction within the image. Methods and results: We performed a feasibility study of creating real-time interactive 3D digital holograms with a purpose-built prototype using intraprocedural data from 3D rotational angiography and live 3D transesophageal echocardiography. The primary objective was to demonstrate that all the anatomical landmarks identified on standard imaging can be similarly identified using dynamic and static holographic images. The secondary objective was to demonstrate the usability of interactions with the image. Parameters were assessed by a rating scale. Eight patients were enrolled of whom five underwent transcatheter ASD closure using 3DTEE and three patients were evaluated by 3D rotational angiography. In all cases dynamic real-time and static 3D holograms were created in standard cath lab conditions. Four individual observers identified all anatomical landmarks on the holographic display independently from the 2D display. Interactions with the hologram including marking, cropping and rotation were performed. There were no adverse events. Conclusions: This study demonstrates, for the first time, the feasibility of generating high quality, clinically relevant, 3D real-time colour dynamic holograms in a standard clinical setting with real patient volumetric data. The impact of computer-generated holography needs to be evaluated in controlled clinical trials.